Prevalence and Genomic Diversity of Salmonella enterica Recovered from River Water in a Major Agricultural Region in Northwestern Mexico - Irvin González-López; José Andrés Medrano-Félix; Nohelia Castro-del Campo; Osvaldo López-Cuevas; Jean Pierre González-Gómez; José Benigno Valdez-Torres; José Roberto Aguirre-Sánchez; Jaime Martínez-Urtaza; Bruno Gómez-Gil; Bertram G. Lee; Beatriz Quiñones; Cristóbal Chaidez (Microorganisms, 2022)
Salmonella enterica is a leading cause of human gastrointestinal disease worldwide. Given that Salmonella is persistent in aquatic environments, this study examined the prevalence, levels and genotypic diversity of Salmonella isolates recovered from major rivers in an important agricultural region in northwestern Mexico. During a 13-month period, a total of 143 river water samples were collected and subjected to size-exclusion ultrafiltration, followed by enrichment, and selective media for Salmonella isolation and quantitation. The recovered Salmonella isolates were examined by next-generation sequencing for genome characterization. Salmonella prevalence in river water was lower in the winter months (0.65 MPN/100 mL) and significantly higher in the summer months (13.98 MPN/100 mL), and a Poisson regression model indicated a negative effect of pH and salinity and a positive effect of river water temperature (p = 0.00) on Salmonella levels. Molecular subtyping revealed Oranienburg, Anatum and Saintpaul were the most predominant Salmonella serovars. Single nucleotide polymorphism (SNP)-based phylogeny revealed that the detected 27 distinct serovars from river water clustered in two major clades. Multiple nonsynonymous SNPs were detected in stiA, sivH, and ratA, genes required for Salmonella fitness and survival, and these findings identified relevant markers to potentially develop improved methods for characterizing this pathogen.